A comparative study of microwave-assisted and conventional heating methods of the synthesis of 1-(Naphthalene-1-Yl)-3-(O, M, P-Tolyl)thioureas, DFT analysis, antibacterial evaluation and drug-likeness assessment - Suhaila Sapari; Emma Izzati Zakariah; Nurul Hidayah Abdul Razak; Insyirah Ramzan; Mohd Sofi Numin; Lee, Yook Heng; Siti Aishah Hasbullah (Penerbit Universiti Kebangsaan Malaysia, 2021)
New isomers of naphthalene-monothioureas, 3a-3c, were synthesized and characterized by using infrared (IR), 1 H and 13 C nuclear magnetic resonance (NMR) and mass spectroscopies (MS). The compounds were obtained from the reaction of o-, m-, p- toluidine with naphthyl isothiocyanate using conventional reflux and microwave-assisted irradiation methods. Microwave-assisted reaction gave higher yields with reduces the reaction time compared to the conventional heating method. Density Functional Theory (DFT) calculations with 6-31G(d, p) basic set at the B3LYP level is carried out to optimize the structure of isomers and calculate the IR, 1 H and 13 C NMR spectra. The DFT B3LYP calculation of FTIR, 1 H and 13C NMR spectra of 3a-3c isomers were in accordance with the experimental data. The calculation of frontier molecular orbitals was also selected to study a relationship as a molecular descriptor in antibacterial activity. The isomers were screened for their in vitro antibacterial activity by using Staphylococcus aureus bacteria. Inhibition activity was displayed for compound 3c with the value of inhibition zone 7 ± 0.34 mm at a concentration of 10 µg/mL. All compounds appeared to be in agreement with Lipinski’s rule of five assessments as they adhered to most of the rules that can be preliminarily classified as active drug-like.